Investigation of heat transfer in combustion chamber of a direct injection diesel engine under different compression ratios and engine torques - GÜMÜŞ, METİN (My University, 2022)
The heat transfer between gases and combustion chamber walls is an important issue because of affecting the emissions and engine performance. On the other hand, there are a number of engine operation parameters impacting on the in-cylinder heat transfer. Of these parameters, compression ratio and engine torque are of significant influence on the engine heat transfer. For this reason, in this study the effects of compression ratio and engine torque on the heat transfer between gases and combustion chamber walls in a compression ignition engine were studied. The most used correlations such as Hohenberg, Woschni, Nusselt, Eichelberg, and Sitkei-Ramanaiah were used to calculate the overall convective heat transfer coefficient in the combustion chamber. Moreover, various heat transfer characteristics (heat flux, heat loss in combustion chamber parts, heat transfer rate) were evaluated in this study. In the performed study, it was shown that compression ratio and engine torque affected significantly the heat transfer coefficient and heat flux. While heat transfer characteristics calculated by Sitkei-Ramanaiah correlation had the highest value, Eichelberg correlation had the lowest values. The most transferred heat among the combustion chamber parts occurred in the piston.

Yanma gazları ve yanma odası duvarları arasında meydana gelen ısı geçişi, emisyonları ve motor performansını etkilediğinden dolayı önemli bir konudur. Diğer taraftan, silindir içi ısı geçişine etki eden birçok motor çalışma parametresi bulunmaktadır. Bunlar arasında motor momenti ve sıkıştırma oranı motor ısı transferinde oldukça etkilidir. Bu sebeple, bu çalışmada sıkıştırma ateşlemeli bir motorda yanma gazları ve yanma odası duvarları arasında meydana gelen ısı transferine motor momenti ve sıkıştırma oranının etkileri incelenmiştir. Yanma odasında genel ısı taşınım katsayısı hesaplanması için literatürde sıklıkla kullanılan Hohenberg, Woschni, Nusselt, Eichelberg ve Sitkei-Ramanaiah bağıntıları kullanılmıştır. Ayrıca, çalışmada çeşitli ısı transferi karakteristikleri (ısı akısı, yanma odası elemanlarında ısı kaybı, birim krank açısında ısı geçişi değişimi) değerlendirilmiştir. Yapılan çalışmada, sıkıştırma oranı ve motor momentinin, ısı taşınım katsayısını ve ısı akısını önemli oranda etkilediği görülmektedir. Sitkei-Ramanaiah bağıntısıyla hesaplanan ısı geçişi karakteristikleri en yüksek değerleri verirken Eichelberg bağıntısı en düşük değerleri vermiştir. Yanma odasında en fazla ısı kaybı pistonda oluşmuştur.
Farklı sıkıştırma oranı ve motor momentlerinde direkt püskürtmeli bir dizel motorun yanma odasında ısı geçişinin incelenmesi
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); General Engineering; Engineering (miscellaneous); Media Technology; Physical Sciences; Heat transfer in combustion chamber; Engine torque; Compression ratio; Convective heat transfer correlations; CYLINDER; MODEL; SURFACES; LOAD; Yanma odasında ısı geçişi; Motor momenti; Sıkıştırma oranı; Isı taşınım katsayıları; Heat transfer in combustion chamber; Engine torque; Compression ratio; Convective heat transfer correlations